Malaysia : Publication of Financial Sector Assessment Program Documentation-Detailed Assessment of Observance of the CPSS-IOSCO Principles for Financial Market Infrastructures. (IMF Staff Country Reports; Country Report ;, 2013)
This report is an assessment of the CPSS-IOSCO Principles for Financial Market Infrastructures (PFMI) in Malaysia. The central bank is in charge of the payment and settlement systems and the Securities Commission (SC) is in charge of regulation and securities. The payment and security systems are elaborated along with the roles of Bursa Malaysia Securities Clearing, Bursa Malaysia Depo, and the Bursa Malaysia Derivative Clearing mechanism. The Executive Board comments that Malaysia shows consistent commitment in the international market and maintains its stance.